Exploring the Nutritional Potential of Jatropha curcas on Body Metabolism: A Bibliometric Analysis - Yuniarti, Elsa; Rosalina, Linda; Fitria, Davina (Frontiers on Healthcare Research, 2024)
Background: a natural source that has great potential as a source of antioxidants is Jatropha curcas (L.). This plant has attracted widespread attention due to its significant content of antioxidant compounds in various parts of the plant, including leaves, seeds, and roots. In addition to health benefits, Jatropha curcas also has applications in various fields, including body metabolism. Methods: This research aims to gain a comprehensive insight into research trends, research collaborations, as well as researchers' contributions in the field of Jatropha's nutritional potential for body metabolism. The research method used is qualitative research with a literature review. Results: The results of overlay visualization in 2021 showed that there were many studies conducted on Jatropha curcas. The level of density in the image is indicated by the number of keywords that often appear and can be marked with yellow Jatropha curcas has not been studied much. This indicates a research gap that exists in current onomastic research so the opportunity to research this topic is still very broad. Conclusion: A contribution to healthcare research can be made by involving Jatropha curcas as a potential source of antioxidants. The health benefits derived from antioxidant compounds found in various parts of this plant, including leaves, seeds, and roots, offer a positive contribution to health research. Additionally, insights into the application of Jatropha curcas in enhancing body metabolism open opportunities for the development of therapies or supplements that can support human health and well-being.